2022
DOI: 10.1177/03057356221096506
|View full text |Cite
|
Sign up to set email alerts
|

Predicting anxiety, depression, and wellbeing in professional and nonprofessional musicians

Abstract: People working in the music industry report significantly higher levels of anxiety and depression than the general population, but to date, studies have not explored the differences between professional musicians and those who perform music primarily for recreation. In this study, 254 musicians from 13 countries completed measures of anxiety, depression, and wellbeing as well as answering questions about their professional status, level of success, and income. Across the whole sample, we found that over half h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Interviewees were not offering medical diagnoses of conditions, but were instead expressing their feelings of anxiety and depression based on a variety of intersecting factors in their lives, of which their methods of relational work represented just one area. Certainly, recent evidence suggests that musicians are highly emotional attuned and that self-reported feelings of mental ill-heath do strongly correlate with clinical diagnoses too (Loveday et al, 2022). In this respect, these findings should be understood as contributing towards a broader area of academic enquiry seeking to bring together a range of psychosocial and cultural emotional triggers in the lives of musicians which are understood as offering one explanatory mechanism vis-à-vis high reported rates of mental ill-health amongst this population (Musgrave, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interviewees were not offering medical diagnoses of conditions, but were instead expressing their feelings of anxiety and depression based on a variety of intersecting factors in their lives, of which their methods of relational work represented just one area. Certainly, recent evidence suggests that musicians are highly emotional attuned and that self-reported feelings of mental ill-heath do strongly correlate with clinical diagnoses too (Loveday et al, 2022). In this respect, these findings should be understood as contributing towards a broader area of academic enquiry seeking to bring together a range of psychosocial and cultural emotional triggers in the lives of musicians which are understood as offering one explanatory mechanism vis-à-vis high reported rates of mental ill-health amongst this population (Musgrave, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This particular dissolution of boundaries is typical of work in the creative industries (Hesmondhalgh & Baker, 2011: 11), where it has been seen that informality is a central feature of this work (Alacovska, 2018); a feature which has been linked to abuses of power and sexual harassment in the absence of formalised regulation with terrible impacts on wellbeing, particularly for women (Hennekam & Bennett, 2017). Indeed, this boundary blurring is further complicated for musicians given that what is work and what is leisure is not always clear, with even the concept of what constitutes being a 'professional' being seen in research to be subjective and not based on metrics which might be typical in other forms of work, such as being paid for example (Loveday et al, 2022). With managers too, definitions of roles and status as colleagues are not always clear.…”
Section: Musicians' Professional Relationships 421 a Second 'Family' ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Better understanding the mental health of musicians has been a growing area of academic enquiry over the previous decade. An emerging body of evidence suggests that musicians experience higher levels of mental ill health than other occupational groups (Detari et al, 2020;Gross & Musgrave, 2016, 2017Loveday et al, 2022;Middlestadt & Fishbein, 1988;Vaag et al, 2016;Wills & Cooper, 1987) and may even have lower life expectancy (Bellis et al, 2012;Kenny & Asher, 2016). A range of factors related to the psychosocial working conditions of musicians have been cited as potential sources of emotional distress (Musgrave, 2022) including financial precarity (Parker, 2015;Berg, 2018), performance anxiety (Kenny et al, 2004;Kenny, 2011;van Kemenade et al, 1995), anti-social working hours (Dobson, 2011), the prevalence of alcohol or substance use (Forsyth et al, 2016), high levels of pressure to succeed (Shorter et al, 2018), the negative impact of musical work on family life (Vaag et al, 2014), missing loved ones whilst touring (Kenny & Ackermann, 2008;Kenny et al, 2012) and the particular challenges and stressors faced by female musicians (Conor et al, 2015;Gross & Musgrave, 2020).…”
Section: Musicians and Mental Healthmentioning
confidence: 99%
“…Loveday et al (2022) in their empirical study exploring music careers as a predictor of anxiety found that “low mental wellbeing in musicians is the result of working as a professional musician, as opposed to being an inherent trait” (p. 1). In other words, our field —our work environments and the beliefs, values, and expectations musicians bring to their activities—contributes to musicians’ increased risk of a range of poor mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%